Pengembangan Tes Keterampilan Gerak Dasar untuk Anak Usia 9-10 Tahun (Kelas III-IV SD) pada Siswa SDN Wonorejo Kecamatan Kunjang Kabupaten Kediri - Umayanah, Umayanah (Universitas Nusantara PGRI Kediri, 2023)
The background of this research is that mastery of basic movement skills possessed during childhood and adolescence is a potential that makes an important contribution in sports activities, games and other physical activities, and can enhance the development of an active lifestyle. Research objectives: (1) Determine test items that can be used as test items to measure basic movement skills in children aged 9-10 years (grades III-IV SD). (2) Testing the level of validity and reliability of basic motor skills test items. (3) Develop basic movement skills test norms as a measuring tool for basic movement skills in children aged 9-10 years (grades III-IV SD). Methods: This research is a development research using a quantitative approach, which focuses on product development in the form of tests of students' basic movement skills. The test was conducted on grade 3 and 4 elementary school students at SDN Wonorejo, Kediri. The test was tested in three stages, namely the small group stage of 27 students, then the medium group stage of 77 students and the large group stage of 234 students. Data analysis used quantitative descriptive. The results showed that in the small group trials, results were obtained with an average test score of 72.6, 74.2, 75.5 and 73.5. Whereas for the medium group it was 73.2, 74.7, 75.8., and 73.7, while for the large group it was 74.3, 75.0, 75.8 and 75.2. Thus, in each group test, a score with a good average category is obtained so that the norms developed on a scale of 1-5 can be used as part of the results of instrument development. From the results of the previous presentation, the following conclusions can be drawn. (1). There are 16 skills test items that can be used as test items in developing basic motor skills test models in children aged 9-10 years (grades III-IV SD). (2) Each test item developed in the motor skills test is a valid and reliable test item, especially in terms of content validity and logical validity as well as construction validity (3). Determination of norms in tests of basic movement skills in children aged 9-10 years (grades III-IV SD) is based on 5 categories namely, 1-5.